Insights into tribology from in situ nanoscale experiments. (11th June 2019) - Jacobs, Tevis D.B.; Greiner, Christian; Wahl, Kathryn J.; Carpick, Robert W.
Abstract: Abstract : Tribology—the study of contacting, sliding surfaces—seeks to explain the fundamental mechanisms underlying friction, adhesion, lubrication, and wear, and to apply this knowledge to technologies ranging from transportation and manufacturing to biomedicine and energy. Investigating the contact and sliding of materials is complicated by the fact that the interface is buried from view, inaccessible to conventional experimental tools. In situ investigations are thus critical in visualizing and identifying the underlying physical processes. This article presents key recent advances in the understanding of tribological phenomena made possible by in situ experiments at the nanoscale. Specifically, progress in three key areas is highlighted: (1) direct observation of physical processes in the sliding contact; (2) quantitative analysis of the synergistic action of sliding and chemical reactions (known as tribochemistry) that drives material removal; and (3) understanding the surface and subsurface deformations occurring during sliding of metals. The article also outlines emerging areas where in situ nanoscale investigations can answer critical tribological questions in the future.